COMPARATIVE STUDIES IN RELIGIOUS SPATIAL PHYSICAL CHARACTERISTICS IN KAMPUNG KAUMAN MALANG, SURAKARTA, AND PEKALONGAN - Junara, Nunik; Triyadi, Sugeng; Budi, Bambang Setia (Journal of Islamic Architecture, 2019)
Kampung Kauman is a representation of Muslim settlements in Indonesia, particularly in Java. The existence of Kampung Kauman in the central district provides its influence over the conditions of the agreement. This study aims to explore the patterns used by the community in efforts to realize the values of Islam in their settlement. Kampung Kauman in Surakarta, Malang, and Pekalongan are selected as part of the similar cities with its dynamics and development. This background of the formation of them has also become one of the considerations. The methodology was a case study,Â  which researchers sought to compare three object regions in the same case. The case was a pattern of the physical characteristics of the settlement. This study shows the differences in religious activities and spatial physic character.Â Â